Hydrogen passivation effect on the conversion efficiency of Si solar cells by low-energy proton implantation. (December 2015) - Parida, Bhaskar; Lim, Gyoungho; Choi, Jaeho; Palei, Srikanta; Kim, Keunjoo
Graphical abstract: This work illustrates low energy hydrogen ion implantation of Si solar cells just before the co-firing process. The cells were hydrogen implanted on the SiN x layer in order to improve the surface passivation and prevent the surface damage by the ion implantation beam. To control the depth of hydrogenated layer, the incident angle of hydrogen ion beam was tilted about 7° from the 〈0 0 1〉 direction and was also twisted 22.5° from the 〈1 1 0〉 direction. The cell implanted with low implantation dose of 10 13 H + /cm 2 and energy of 4 keV showed highest efficiency of 18.02% due to the excellent surface passivation property, high photocurrent and minority carrier lifetime as compared to the reference and other implanted silicon solar cells. Highlights: We fabricated Si solar cell by hydrogen implantation with low energy. We examine changes in the energy level and the ion concentration. Decreasing energy will increase cell quality if the concentration is same. Decreasing concentration will increase cell quality if the energy is same. Implantation effects depend on the surface passivation about cell efficiency improvement. Abstract: We investigated the hydrogen passivation effect on the conversion efficiency of Si solar cells by including low-energy hydrogen ion implantation in the cell fabrication process. The solar cells were implanted with various proton energies and doses just before the co-firing process. The quantum efficiency specifically in the blue wavelengths of the solar cells increased with a low implantation dose and energy indicating improvement of surface passivation. However, quantum efficiency decreased when the implantation dose and energy were increased, indicating a high defect-assisted surface recombination of minority carriers. The cells implanted with a low dose and energy in the presence of SiN x showed interfacial passivation with enhanced photocurrent, minority carrier lifetime and short-circuit current density for improved conversion efficiency.